Analisa Investasi Pengadaan Alat Support Tambang (Bulldozer D8R) Untuk Efisiensi Kinerja Bulldozer D10T Pt Cipta Kridatama Job Site PT. Adimitra Baratama Nusantara, Sanga-Sanga, Kutai Kartanegara. - Rijabul Mulia; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. During the excavation at the ABN site, PT CK was located in Kampung Jawa Village, Sanga-sanga District and Muara Kembang Village, Muara Jawa Subdistrict, Kutai Kartanegara District, East Kalimantan using a ripping unit with D10T bulldozer unit in breaking rocks. The purpose of ripping is to make the overburden material easier to dig by the loader and easy to haul by the conveyor. Looking at the open pit mining system where the Dozzer D10T is the main unit and is still used as a unit of support in achieving production targets, the authors